DISCOVERING MARINDUKANON RECREATIONAL GAMES AS INPUT FOR LEARNING MODULE IN PHYSICAL EDUCATION; BASES FOR CURRICULUM ENHANCEMENT - LABAGUIS, GENIL (International Journal of Arts, Sciences and Education, 2022)
This study aimed to develop a learning module in physical education subject in the content of physical fitness and recreational activities. The researcher employed a qualitative research method using a case study type of research design. Employing the input-process-output as the conceptual framework, this study was conducted in the province of Marinduque in three (3) towns namely; Mogpog, Gasan, and Santa Cruz. With an adopted and modified questionnaire, the learning module was developed among the selected adults who describe recreational games based on their experiences in terms of type, mechanics, requirements and its influence to physical and psychosocial wellbeing. Same as to children executed and found the effect of recreational games to their physical, social, and psychological wellbeing. Moreover, the Mapeh teacher checked, evaluated and assessed the content of learning module to be used in physical education subject of department of education. The result revealed that recreational games have an effect to the physical, social, and psychosocial wellbeing. The study then concluded that the developed learning module may be used as instructional materials for physical education curriculum in the department of education especially for elementary grade level 4, 5, 6, and 10 either public or private school in the Philippines.